2020
DOI: 10.3389/fimmu.2020.01557
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Signaling Mediated by TSLP and IL-7 in Inflammation, Autoimmune Diseases, and Cancer

Abstract: Thymic Stromal Lymphopoietin (TSLP) and Interleukin-7 (IL-7) are widely studied cytokines within distinct branches of immunology. On one hand, TSLP is crucially important for mediating type 2 immunity at barrier surfaces and has been linked to widespread allergic and inflammatory diseases of the airways, skin, and gut. On the other hand, IL-7 operates at the foundations of T-cell and innate lymphoid cell (ILC) development and homeostasis and has been associated with cancer. Yet, TSLP and IL-7 are united by key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 190 publications
(216 reference statements)
0
34
0
Order By: Relevance
“…Correspondingly, the inhibition of IL-6 transsignaling, wherein the complex of IL-6 and sIL-6R can stimulate cells that do not express IL-6R (such as endothelial cells and smooth muscle cells), is sufficient to block disease in mouse models of inflammatory bowel disease and RA ( 40 ). IL-10 is primarily an anti-inflammatory cytokine ( 37 ); IL-27 is a negative regulator of IL-12 ( 38 ); TSLP is a “master switch” for allergic inflammation ( 41 ); and MMP-3 can degrade extracellular matrix proteins and aggravate the inflammatory response ( 42 ). Importantly, increased MMP-3 levels have also been observed in supraspinous ligament samples from AS patients, whereas the degradation of extracellular matrix components is a pathological feature of chronic arthritis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the inhibition of IL-6 transsignaling, wherein the complex of IL-6 and sIL-6R can stimulate cells that do not express IL-6R (such as endothelial cells and smooth muscle cells), is sufficient to block disease in mouse models of inflammatory bowel disease and RA ( 40 ). IL-10 is primarily an anti-inflammatory cytokine ( 37 ); IL-27 is a negative regulator of IL-12 ( 38 ); TSLP is a “master switch” for allergic inflammation ( 41 ); and MMP-3 can degrade extracellular matrix proteins and aggravate the inflammatory response ( 42 ). Importantly, increased MMP-3 levels have also been observed in supraspinous ligament samples from AS patients, whereas the degradation of extracellular matrix components is a pathological feature of chronic arthritis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identi cation of IL7R has made great strides in understanding the MS genetic risk factors (28). Increasing evidence has shown that this gene also promotes oligodendrocyte survival and myelination (29). Lei et al, have used metronidazole-induced demyelination in a transgenic zebra sh line in which oligodendrocytes expressed green uorescent protein (GFP).…”
Section: Discussionmentioning
confidence: 99%
“…Short TSLP is constitutively present in many tissues where it plays a homeostatic role, whilst the production of the long isoform can be induced by proinflammatory stimuli and is increased in asthmatic patients [ 31 ]. The long variant of TSLP exerts its biological functions by selectively binding to its cognate receptor (TSLPR), and this interaction is promoted by the electrostatic attraction occurring between the positive charges of TSLP surface and the negative charges of TSLPR [ 32 , 33 ]. The resulting TSLP/TSLPR binary molecular aggregate in turn recruits the α subunit of the IL-7 receptor (IL-7Rα).…”
Section: Pathogenic Role Of Tslp In Asthmamentioning
confidence: 99%
“…The resulting TSLP/TSLPR binary molecular aggregate in turn recruits the α subunit of the IL-7 receptor (IL-7Rα). As a consequence, the assembly of the extracellular ternary complex TSLP/TSLPR/IL-7Rα leads to activation of an intracellular signaling network including Janus kinases 1 and 2 (JAK1/2), signal transducers and activators of transcription 3 and 5 (STAT3/5), as well as nuclear factor κB (NF-κB), mitogen-activated protein kinases (MAPK), and phosphoinositide 3 kinase (PI3K) ( Figure 2 ) [ 31 , 32 , 33 ]. These signaling pathways lead to activation of genes encoding Th2 cytokines such as IL-4, IL-5, IL-9, and IL-13.…”
Section: Pathogenic Role Of Tslp In Asthmamentioning
confidence: 99%